Separating innovation short-run and long-run technical efficiencies: Evidence from the Economic Community of West African States (ECOWAS) - (:unkn) unknown (My University, 2022)
A stream of literature has been developed on the measurement of the efficient production of innovation, that is, innovation technical efficiency. However, the efficiency measured is quite fuzzy as no distinction is made between innovation short-run and long-run efficiencies. Also, African economies have been heavily neglected, despite the need to explore ways to improve the poor levels of innovation they usually exhibit. In this paper, we measure innovation technical efficiency by separating short-run and long-run efficiencies. Overall technical efficiency, that is, efficiency both in the short and long run is also assessed. The empirical evidence makes use of data from countries from the Economic Community of West African States, one of the most important economic areas in Africa. To obtain efficiency scores, we carry out a stochastic frontier analysis. Results show that research and development, market sophistication and human capital significantly influence innovation output. No country is found to be efficient following one of the types of efficiency. The long-run and average short-run efficiencies over the study period are not similar, which shows the need to separate the types of efficiency. Domestic credit to private sector and governance are highlighted as determinants of innovation efficiency. Some policies are suggested based on these findings.
Keywords: African Research